PENDAMPINGAN SISWA/I MUKHTARI VITTHAYA SCHOOL PADA PETERNAKAN PERKEMBANGBIAKAN INDUK LEBAH DI BANSUAN CHAONRONG CHOENGKHAO NARATHIWAT THAILAND: MENTORING MUKHTARI VITTHAYA SCHOOL STUDENTS ON BEE BROOD BREEDING FARM IN BANSUAN CHAONRONG CHOENGKHAO NARATHIWAT THAILAND - Safarah Fauziah Rahmi; Aidil Syah Putra (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The "stingless" bee is a small insect that does not have a stinging device on its tongue, therefore this name is called the "stingless" bee. In beekeeping in general, beekeepers do not choose such types of flowers as other bees. So that the honey produced by beekeepers is a combination of various flowers and nectar of herbal plants to become quality water with a delicious sour taste. This community service activity aims to increase the knowledge and understanding of Mukhtari Vitthaya School students in the process of breeding mother bees in Tambon Mari Abotok village, Amphoe Ra-Ngae, Narathiwat Province. This method of mentoring activities is carried out by applying direct assistance and observation on mother bee breeding farms until Mukhtari Vitthaya School students can understand well and correctly. That way, the results of this mentoring activity foster students' curiosity, so as to form a broader insight into the breeding of bee brood.